2021
DOI: 10.4315/jfp-20-330
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding a Postbiotic Derived from Saccharomyces cerevisiae Fermentation as a Preharvest Food Safety Hurdle for Reducing Salmonella Enteritidis in the Ceca of Layer Pullets

Abstract: Salmonella Enteritidis is responsible for a significant proportion of foodborne Salmonellosis in the United States and continues to be attributable to table eggs, despite increased federal oversight in recent years. Technologies, including feed additives, continue to be evaluated for pre-harvest application of their potential food safety benefits. Here, Diamond V Original XPC™, a Saccharomyces cerevisiae fermentation based postbiotic (SCFP), was evaluated for its effectiveness in the reduction of Salmonella En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Our results are also in agreement with other studies that demonstrated that postbiotic supplementation is associated with improved microbiome balance which has been translated into host health in many species (23,60,62,63). In horses, postbiotic supplementation resulted in increased relative abundances of fibrolytic bacteria (64) and attenuated exercise-induced stress markers (28).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also in agreement with other studies that demonstrated that postbiotic supplementation is associated with improved microbiome balance which has been translated into host health in many species (23,60,62,63). In horses, postbiotic supplementation resulted in increased relative abundances of fibrolytic bacteria (64) and attenuated exercise-induced stress markers (28).…”
Section: Discussionsupporting
confidence: 92%
“…Controlled research evaluating the effects of SCFP to reduce Salmonella Enteritidis challenges has demonstrated quantitative reductions in cecal contents [ 62 , 63 ]; however, reductions in prevalence (% positive) for direct challenge studies are commonly not observed due to extremely high challenge doses administered via oral gavage. Real-world industry conditions have exposure routes and doses which vary greatly [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to probiotics, postbiotics involve the use of non-viable bacteria or bacterial metabolic products such as inactivated cells, enzymes, exopolysaccharides, plasmalogens, organic acids, short-chain fatty acids, and peptides, mainly (but not exclusively) produced from lactic acid bacteria due to their multiple metabolic abilities [ 59 ]. Some of the benefits offered by postbiotics, when used in poultry, include the direct or indirect control of pathogens such as Salmonella and their negative effects ( Table 4 ).…”
Section: Feeding-based Strategies To Control Salmonella Infection In Poultrymentioning
confidence: 99%